Relation between benign course of multiple sclerosis and low-grade humoral immune response in cerebrospinal fluid. Issue 2 (February 1980) - Stendahl-Brodin, L; Link, H
Abstract : The prognosis in multiple sclerosis (MS) is related to the presence of an abnorma humoral immune response within the central nervous system: 14/17 MS patients (82%) without oligoclonal CSF IgG displayed no or slight disability after a mean duration of MS of 17 years, while 53% of 88 patients with oligoclonal CSF IgG had a benign course after a mean duration of 13 years (p less than 0.05). A benign course also was more often accompanied by a normal CSF IgG index. MS patients without oligoclonal CSF IgG had elevated CSF/serum ratios of albumin in 6%, and of the complement factors C3 in 0% and C4 in 6%, as against 20%, 27% and 37%, respectively, in MS patients with oligoclonal CSF IgG.